1979
DOI: 10.1159/000119802
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography of Sturge-Weber Disease

Abstract: Findings in computed tomography (CT) with or without contrast infusion were analyzed in 8 patients with Sturge-Weber disease. From the extent of calcification in the CT, Sturge-Weber disease can be classified into two types, localized and diffuse. The extent of calcification or cortical atrophy is predictable, if it can be shown that enhanced areas in contrast infusion CT truly represent leptomeningeal angiomatos¡s. Thus, using enhanced CT, the capacity of prediction as to whether the patient will have a local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Whether the contrast enhancement represents leptomeningeal angiomatosis or leakage of contrast material into the brain due to a permeability defect of abnormal vessels, is difficult to determine. If it can be shown that enhanced areas in contrast infusion CT truly represent leptomeningeal angiomatosis, Sturge-Weber disease is likely to be diagnosed early in the newborn period using enhanced CT, and the extent of calci fication or cortical atrophy is probably predictable [12], CT is the neuro radiological procedure of choice to evaluate patients with Sturge-Weber disease. In our limited experience, it seems noteworthy to emphasize that some clinical criteria such as personal and past history, physical and neurological examination, EEG findings and clinical features of epilepsy are not a reliable guide to the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the contrast enhancement represents leptomeningeal angiomatosis or leakage of contrast material into the brain due to a permeability defect of abnormal vessels, is difficult to determine. If it can be shown that enhanced areas in contrast infusion CT truly represent leptomeningeal angiomatosis, Sturge-Weber disease is likely to be diagnosed early in the newborn period using enhanced CT, and the extent of calci fication or cortical atrophy is probably predictable [12], CT is the neuro radiological procedure of choice to evaluate patients with Sturge-Weber disease. In our limited experience, it seems noteworthy to emphasize that some clinical criteria such as personal and past history, physical and neurological examination, EEG findings and clinical features of epilepsy are not a reliable guide to the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…1). One 39-year-old died of ocular melanoma, but no information about precedent ocular melanosis was offered (21). Almost 50% of patients with phakomatosis pigmentovascularis type lib and SWS aiso have nevus flammeus involviog the extremities (17)(18)(19)(20).…”
Section: Clinical Appearancementioning
confidence: 99%
“…This has now become the diagnostic test in Sturge-Weber syndrome [2,6,14]. In infancy it shows calcification and atrophy on the involved side at a time when skull X-rays are normal.…”
Section: Computed Tomographic Scanmentioning
confidence: 99%